2015
DOI: 10.21608/aeji.2015.17816
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Relationship between Blood Ammonia Level and Esophageal Varices in Patients with Liver Cirrhosis

Abstract: were done for all patients and control subjects. Results: There was a highly significant increase in the mean values of blood ammonia in cirrhotic patients with varices in comparison to other patients without varices, with highly significant positive correlation between serum ammonia and size of varices. There was a significant increase in the mean values of blood ammonia in cirrhotic patients with grade III and IV varices [large varices) in comparison to cirrhotic patients with grade I and II varices. Conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
3
0
4
Order By: Relevance
“…Measurement of blood ammonia revealed that it was significantly higher in patients with EV than in those without EV (p<0.001). Our finding is congruent with that of Ali et al (16), who also detected an increase in the mean values of blood ammonia in patients suffering from cirrhosis with varices in comparison to patients without varices.…”
Section: Discussionsupporting
confidence: 93%
“…Measurement of blood ammonia revealed that it was significantly higher in patients with EV than in those without EV (p<0.001). Our finding is congruent with that of Ali et al (16), who also detected an increase in the mean values of blood ammonia in patients suffering from cirrhosis with varices in comparison to patients without varices.…”
Section: Discussionsupporting
confidence: 93%
“…Blood ammonia was significantly higher among patients with EV than controls ( P = 0.001). Other studies have found this relation between the presence of varices and elevated blood ammonia and even suggested a blood ammonia cutoff value for prediction of variceal presence [ 15 , 28 – 30 ]. This can be explained by the role ammonia plays in production of portal hypertension and hence development of varices [ 18 ].…”
Section: Discussionmentioning
confidence: 79%
“…These results came in agreement with Sharma et al (2017) that found that there was no significant difference between esophageal and gastric varices regarding platelets. Also, agreed with the study conducted by Rezayat et al (2014) who evaluated changes of doppler indices in gastric varices patients with and without gastroesophageal varices.On the other hands, Ali et al (2015) found that there was a significant decrease in the mean values of platelet count/ spleen diameter ratio in cirrhotic patients with gastric varices in comparison to other patients without gastric varices. In the current study, splenic vein diameter, splenic vein cross sectional area, and splenic congestion index significantly increased among group Ca and group Cbthan group A and group B, and this came in concordance with the study of Esmat et al (2012) who found a statistically significant correlation between the presence and grade of gastroesophageal varices with the splenic diameter, and also was in concordance with results of Rezayat et al (2014) who found that in half of patients with portal hypertension the splenic vein diameter increases to more than 10 mm.…”
Section: Discussionmentioning
confidence: 88%